Development and Prospect of Axial Field Permanent Magnet Machine - KE Siqin (Kongzhi Yu Xinxi Jishu)
Because of shorter axial dimension and higher specific torque, axial field permanent magnet (AFPM) machine is very suitable for the applications that axial space is limited and low speed and direct drive is required. It described the features of AFPM machine, presented its recent development status and prospect. AFPM machine will be used and bring technical innovations in many fields.